Berpetualang Bersama Si Kancil Untuk Meningkatkan Kemampuan Berbahasa Siswa Taman Kanak-Kanak Usia 5-6 Tahun - Aufi Hidayatul Azmi; Deby Melisa Putri; Fatma Azira; Miftahur Rizqi (Observasi : Jurnal Publikasi Ilmu Psikologi, 2024)
Language plays an important role in children's daily lives as it is a communication tool that connects individuals in society. Language skills are the foundation for a child that is naturally acquired to adapt to their environment, as a tool to socialise and a way to respond to others. This study set out to ascertain how the roleplaying approach affected the language development of young children. One group pretest postest design is the research design that the investigators utilized. This method is carried out to take measurements before (pretest) and after (posttest) giving treatment. Because the situation before the treatment can be compared, the outcomes of the treatment can be known with more accuracy. Based on the results of the study, the results show that there is a significant influence between before and after treatment. Based on the data analysis in this study, researchers can conclude that there is a significant effect of the treatment given on the language skills of Kartika I-57 Bukittinggi kindergarten students. This is based on the results of the Independent Samples Test which shows a significance value (Sig.) of 0.001, which is smaller than 0.005. This result shows a significant difference between the pretest and posttest results, so the intervention method applied in the meeting session is effective in improving children's language development. In addition, the results of normality and homogeneity tests showed that the data were normally distributed and the research subjects had homogeneous characteristics.   Keywords: Language plays an important role in children's daily lives as it is a communication tool that connects individuals in society. Language skills are the foundation for a child that is naturally acquired to adapt to their environment, as a tool to socialise and a way to respond to others. This study set out to ascertain how the roleplaying approach affected the language development of young children. One group pretest postest design is the research design that the investigators utilized. This method is carried out to take measurements before (pretest) and after (posttest) giving treatment. Because the situation before the treatment can be compared, the outcomes of the treatment can be known with more accuracy. Based on the results of the study, the results show that there is a significant influence between before and after treatment. Based on the data analysis in this study, researchers can conclude that there is a significant effect of the treatment given on the language skills of Kartika I-57 Bukittinggi kindergarten students. This is based on the results of the Independent Samples Test which shows a significance value (Sig.) of 0.001, which is smaller than 0.005. This result shows a significant difference between the pretest and posttest results, so the intervention method applied in the meeting session is effective in improving children's language development. In addition, the results of normality and homogeneity tests showed that the data were normally distributed and the research subjects had homogeneous characteristics.